2018
DOI: 10.1111/1753-0407.12642
|View full text |Cite
|
Sign up to set email alerts
|

Utility of three novel insulin resistance‐related lipid indices for predicting type 2 diabetes mellitus among people with normal fasting glucose in rural China

Abstract: Prediction of T2DM was not improved by TyG, VAI, and LAP versus FPG or WC alone. Therefore, TyG, VAI, and LAP may not be inexpensive tools for predicting T2DM in rural Chinese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
1
38
2
1
Order By: Relevance
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…compared the TyG index with the euglycemic‐hyperinsulinemic clamp test, and suggested that TyG could be useful for the identification of individuals with decreased insulin sensitivity in 2010 . A series of cohort and cross‐sectional studies confirmed a strong correlation between the TyG index and IR, type 2 diabetes mellitus, MetS, hypertension, cardiovascular events and fatty liver both in China and elsewhere. Published studies have shown that the TyG index is helpful for the prediction and early identification of individuals at high risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, TyG has been compared to HOMA‐IR and HEC, and studies have suggested that TyG could be a surrogate for identifying IR Subsequently, a series of clinical studies confirmed a strong association between TyG and T2D, metabolic syndrome, hypertension, and cardiometabolic diseases . Zheng et al conducted a longitudinal study with 4686 subjects followed up for 9 years and demonstrated that TyG could predict incident hypertension among the Chinese population .…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, TyG has been compared to HOMA-IR and HEC, and studies have suggested that TyG could be a surrogate for identifying IR 12,31 Subsequently, a series of clinical studies confirmed a strong association between TyG and T2D, metabolic syndrome, hypertension, and cardiometabolic diseases. 32,33 Zheng et al conducted a…”
Section: Ir-compensatory Hyperinsulinemia Induces Carotid Body Overacmentioning
confidence: 99%
“…For anthropometric indices associated with metabolic risk, sex-specific cutoff values of BMI, WC, and WHtR are 24.12 kg/m 2 , 83.5 cm and 0.51 for males and 23.53 kg/m 2 , 77.5 cm and 0.49 for females, respectively, as derived from the Chinese elderly population [21]. Furthermore, sex-specific cut-off values of VAI and LAP associated with impaired glucose metabolism are 2.25 and 36.96 for Chinese males and 2.5 and 37.84 for Chinese females, respectively [29]. Hypertension is defined as SBP ≥ 140 mmHg and/or DBP ≥ 90 mmHg.…”
Section: Methodsmentioning
confidence: 99%